Effect of Virgin Coconut Oil from Green Coconut on High-Density Lipoprotein (HDL) Levels in Blood Serum of White Mice - Iswendi Iswendi; Iryani Iryani; Regi Fadila Putra (EKSAKTA: Journal of Sciences and Data Analysis, 2021)
This study aims to determine the effect of High-Density Lipoprotein (VCO) dose on mice's blood serum High-Density Lipoprotein (HDL) levels. This study is an experimental study using 24 mice divided into four groups. Control (-), Control (+) were fed egg yolks 0.025 mL/g body weight, Dose 0.02 and Dose 0.025 were experimental groups, given egg yolks 0.025 mL/g mice body weight and VCO at a dose of 0.020 mL, and 0.025 mL/g body weight of mice. HDL levels were determined on days 7, 14, and 21 by enzymatic method using 20 D* spectrophotometry. The statistical test found that the length of time giving VCO significantly affected blood serum HDL levels in mice with Fcount > Ftable (Fcount = 7.128 and Ftable = 5.14). In contrast, variations in VCO dose did not significantly affect blood serum HDL levels. mice with Fcount < Ftable (Fcount = 3.33 and Ftable = 4.76). The highest HDL level was at a dose of 0.020 mL/g body weight of mice with a treatment period of 14 days, namely 164,033 mg/dL of blood.